2016
DOI: 10.1016/j.anireprosci.2016.02.028
|View full text |Cite
|
Sign up to set email alerts
|

Non-viable sperm in the ejaculate: Lethal escorts for contemporary viable sperm

Abstract: Non-viable sperm ("dead sperm") are present in variable numbers in mammalian ejaculates and their number increase substantially when semen is stored, particularly cryopreserved. This review comparatively highlights, with experimental data in porcine, the role-played by non-viable sperm in the outcome of semen used in assisted reproductive technologies. As well, the review discusses our current understanding of their origin and the pathways involved when their large numbers negative influence the functional lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
39
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 73 publications
0
39
0
Order By: Relevance
“…The authors suggest that differences in the biochemical components of the HEY, OEY, or LPFo could account for the marked variations in sperm cryo-survival. Another possible explanation for this phenomenon could be the high proportions of dead frozen-thawed spermatozoa in the lactose-OEY-G extender, which might be an additional source of production of reactive oxygen species (ROS) resulting in compromised sperm viability and DNA integrity (Roca et al, 2016). Similar assumptions have been suggested for the wide variations in cryo-induced sperm DNA damage for boar semen frozen in various avian egg yolk-based extenders (Strzeżek et al, 2014;Fraser et al, 2016).…”
mentioning
confidence: 76%
“…The authors suggest that differences in the biochemical components of the HEY, OEY, or LPFo could account for the marked variations in sperm cryo-survival. Another possible explanation for this phenomenon could be the high proportions of dead frozen-thawed spermatozoa in the lactose-OEY-G extender, which might be an additional source of production of reactive oxygen species (ROS) resulting in compromised sperm viability and DNA integrity (Roca et al, 2016). Similar assumptions have been suggested for the wide variations in cryo-induced sperm DNA damage for boar semen frozen in various avian egg yolk-based extenders (Strzeżek et al, 2014;Fraser et al, 2016).…”
mentioning
confidence: 76%
“…Martin-Muñoz et al [33] demonstrated assessing these markers to determine the differential effect of ROS during cryopreservation on stallion sperm and the importance of ROS homeostasis in the selection of ejaculates for freezing. The elimination of non-viable sperm from a sample could be important in ROS homeostasis since the dead sperm are known to have a negative effect on the viable subpopulation [9]. In addition, Roca et al [34] showed that high proportions of dead sperm in raw semen samples before and during freezing induce significantly increased ROS generation and nuclear DNA fragmentation in frozen-thawed sperm.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most important objectives of conservationist projects is to store as many high-quality samples as possible. Sperm selection optimizes the use of available space, allowing us to select useful cells (viable and motile sperm) and discard non-viable, apoptotic and non- motile sperm that impair the quality of the sample [9]. …”
Section: Introductionmentioning
confidence: 99%
“…Because the ejaculate contains a heterogeneous suspension of spermatozoa, sperm sub-populations of different quality and functionality are present (8). D'Amours et al (9) suggested that qualitative and/or quantitative differences in protein expression among these sperm subpopulations probably resulted in an unbalanced interaction between spermatozoa and the changing surrounding environment during ejaculation.…”
mentioning
confidence: 99%